Solid Pseudopapilar Neoplasm of the Pancreas: Case Report and Literature Review - Rosas-Zamora, A J; Falcón-Cancino, Luis Arturo; Ramírez-Vázquez, J L; López-Bernal, C; Ochoa-Cruz, N; Hernández-Moran, A A; Padrón-Arredondo, G (British Journal of Healthcare and Medical Research, 2023)
Introduction: Solid pseudopapillary tumor of the pancreas is also called Frantz tumor. The World Health Organization classified it as a solid pseudopapillary neoplasm in 1996. It is more frequent in young or black Asian women, between 20 and 40 years of age, although there are isolated cases in children and men. Case Report: 24 year-old female. With a history of hemolytic anemia being treated by Hematology. The physical examination was unremarkable. Ultrasound revealed a tumor in the body and tail of the pancreas. In view of these findings, the radiological study was completed with a CT and MRI, having a suspected diagnosis of a pseudopapillary tumor, surgical treatment was performed with subsequent follow-up by medical oncology. Discussion: This type of tumor usually has nonspecific clinical manifestations, most of them caused by compression of the tumor to the normal pancreatic parenchyma. About 15% of patients are asymptomatic. It has not been possible to clearly establish which cells are involved in their development; they seem to be derived from totipotential stem cells from the genital ridges that attach to the pancreas during embryogenesis. It has been related to mutations in chromosome 11q, which contains genetic material for the formation of proteins such as cyclin D1, FLI-1, CD56, and the progesterone receptor. Conclusions: Solid pseudopapillary neoplasm is a rare low-grade malignant entity that mainly affects young women. In most cases it is asymptomatic, so it is often diagnosed incidentally.